THE IMPACT OF INTERNATIONAL TRADE LIBERALIZATION ON IMPORT-EXPORT GROWTH IN FIVE ASEAN COUNTRIES - Melti Roza Adry (TRANSACTION: Journal of Taxation, Accounting, Management and Economics, 2023)
Trade liberalization or free trade is a condition in which a country engages in trade with other nations without any barriers. The process towards achieving free trade is referred to as trade liberalization. One of the goals of trade liberalization is to promote economic growth by capturing both static and dynamic benefits of trade through more efficient allocation of resources. This research aims to examine the impact of international trade liberalization on export-import growth in five ASEAN countries. The study employs a qualitative descriptive research approach using literature review methods, drawing information from previous research journals and utilizing data obtained from the World Bank. The research is conducted in five ASEAN countries: Indonesia, Malaysia, the Philippines, Singapore, and Thailand. The results of this research explain that trade liberalization and economic openness provide access to knowledge for developing countries and create a more competitive environment, forcing domestic producers to improve the quality of their products to remain competitive with foreign producers. Trade liberalization is associated with opening market access for a country's export products to the world. The increasing foreign investment leads to a rising flow of investment profits (income) to foreign countries